A Communication Audit Exercise to Enhance Virtual Team and Individual Communication Skills. (December 2021) - Bailey-Hughes, Brenda
This article outlines a unique student activity designed to close the gap between students' perceived and actual communication and team behavior during virtual group meetings. The Communication Audit exercise requires that students record an online small group meeting and then review the recording while categorizing each verbal remark into observable behaviors aligned to the instructor's learning objectives. The audit delivers objective data to students concerning their team habits and leads to excellent discussions of opportunities to improve team dynamics and individual contributions to a team process.